New Applications of a Kind of Infinitesimal-Operator Lie Algebra - Honwah Tam; Yufeng Zhang; Xiangzhi Zhang (Advances in Mathematical Physics)
Applying some reduced Lie algebras of Lie symmetry operators of a Lie transformation group, we obtain an invariant of a second-order differential equation which can be generated by a Euler-Lagrange formulism. A corresponding discrete equation approximating it is given as well. Finally, we make use of the Lie algebras to generate some new integrable systems including (1+1) and (2+1) dimensions.